2021
DOI: 10.3928/24748307-20211104-01
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Access to Care in Cancer Screening Among Korean Americans

Abstract: Background: Health literacy and access to care are critical facilitators for preventive health behaviors. After the passage of the Affordable Care Act in March 2010, little has been studied about how improved health insurance coverage has impacted the use of preventive health services among Korean Americans. Objective: The study assessed the impact of access to care, use of services, and health literacy on cancer screening among Korean Americans. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…The increase in BC prevalence among these women is likely related, at least in part, to their low BC screening rates that are influenced by their health beliefs regarding BC screening [ 4 6 ]. Even though the American Cancer Society (ACS) recommends a yearly mammogram for women aged 40 years or more, recent studies reported that about 10–53% of KA women had a mammogram in the last 2 years, and about 10–29% never had a mammogram in their lifetimes [ 5 7 ]. Early BC screening starting at age 40 is especially important for these women.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in BC prevalence among these women is likely related, at least in part, to their low BC screening rates that are influenced by their health beliefs regarding BC screening [ 4 6 ]. Even though the American Cancer Society (ACS) recommends a yearly mammogram for women aged 40 years or more, recent studies reported that about 10–53% of KA women had a mammogram in the last 2 years, and about 10–29% never had a mammogram in their lifetimes [ 5 7 ]. Early BC screening starting at age 40 is especially important for these women.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Korean Americans are one of the fastest growing ethnic groups in the US, and 59% of them are first-generation with limited English proficiency, which limits access to quality health care and increases health inequities. [13][14][15][16][17] Consequently, Korean Americans are at considerable risk for cardiovascular disease, including hypertension (31%-53%), type 2 diabetes (8%-20%), and obesity (45%-56%). 11,[18][19][20][21][22] To reduce health disparities related to low levels of PA among minoritized racial and ethnic populations, it is essential to implement PA interventions that consider the unique cultural values and norms of the specific target population.…”
mentioning
confidence: 99%
“…Korean Americans are one of the fastest growing ethnic groups in the US, and 59% of them are first-generation with limited English proficiency, which limits access to quality health care and increases health inequities 13–17. Consequently, Korean Americans are at considerable risk for cardiovascular disease, including hypertension (31%-53%), type 2 diabetes (8%-20%), and obesity (45%-56%) 11,18–22…”
mentioning
confidence: 99%